2019
DOI: 10.31989/ffhd.v9i8.644
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid profile, phenolic compounds and potential antioxidant activity of fresh and cooked Massaman curry paste

Abstract: Background: Fresh herbs and spices used in Thai food are one of the aspects that make Thai cuisine so unique. While some of these herbs and spices  have been studied scientifically to look for health benefits, there is little definitive evidence on the subject.Objective: To determine the proximate compositions, fatty acid profiles, phenolic and flavonoid contents, and antioxidant activity of fresh massaman curry paste (MCP) and cooked massaman curry, including beef and chicken massaman curry (BMC and CMC, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Linoleic acid (C18:2, 35.44–51.37%) and oleic acid (C18:1, 18.29–24.04%) were the most abundant fatty acids in SD1, SD2, SD3, SD4, SD5, and SD6. The C18:2 has been shown to lower blood cholesterol and prevent atherosclerosis ( 25 ). The content of C18:2 in SD ranged from 89.16 to 265.56 mg/g, suggesting its hypolipidemic potential.…”
Section: Resultsmentioning
confidence: 99%
“…Linoleic acid (C18:2, 35.44–51.37%) and oleic acid (C18:1, 18.29–24.04%) were the most abundant fatty acids in SD1, SD2, SD3, SD4, SD5, and SD6. The C18:2 has been shown to lower blood cholesterol and prevent atherosclerosis ( 25 ). The content of C18:2 in SD ranged from 89.16 to 265.56 mg/g, suggesting its hypolipidemic potential.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the spicy basil leaf curry expressed higher antioxidant activity values than Massaman curry in all assays (p < 0.05) (Table 2). Dat-arun et al [8] reported that fresh Massaman curry paste provided DPPH with 11.81 ± 0.06 mg GAE/100 g crude extract and FRAP with 0.311 ± 0.006 mg TE/100 g crude extract. However, to date, no scientific information on spicy basil leaf curry is available.…”
Section: Total Phenolic and Flavonoid Contents And Antioxidant Activi...mentioning
confidence: 99%
“…Historically, Thais have used herbs and spices and even curry paste containing galangal rhizomes, chili pods, garlic bulbs, peppers, shallots, and coriander seeds, with health benefits linked to their anti-aging, anti-inflammation, anti-cancer, and antioxidation properties [3][4][5], to treat or relieve common complaints such as stomachache, flu, and acne, following ancestral traditions [6]. Scientific data have shown that phenolic compounds, especially ferulic acid and flavonoids, are antioxidant agents [7,8] that inhibit reactive oxygen species (ROS) and related molecules such as nitric oxide, nitric oxide synthase, and xanthine oxidase, as well as toxic agents produced from free radicals [9]. Allicin derived from crushed or damaged garlic has anti-cancer properties [10], while eugenol plays a key role in antioxidant and antimicrobial activity [11], and the procyanidin oligomer obtained from cinnamon exhibits anti-diabetes properties [12].…”
Section: Introductionmentioning
confidence: 99%